Hypogeococcus pungens Granara de Willink (Insecta: Hemiptera: Pseudococcidae), a Mealybug - Amanda Hodges; Greg Hodges (EDIS, 2009)
EENY-459, a 5-page illustrated fact sheet by Amanda Hodges and Greg Hodges, is part of the Featured Creatures collection. It describes this mealybug native to South America, which is sometimes confused with pink hibiscus mealybug, but has far fewer potential hosts — its synonymy, distribution, identification characteristics, life cycle, hosts, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.